Analisis Gaya Bahasa Personifikasi Terhadap Novel “Orang-Orang Biasa” Karya Andrea Hirata - Ester Mariam Silaban; Achmad Yuhdi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This research aims to describe and explain the form of language style used in Andrea Hirata's Ordinary People novel, one of which is the personification style contained in Andrea Hirata's Ordinary People novel. The approach in this study uses descriptive qualitative with data as the source of the novel Ordinary People by Andrea Hirata. The data collection technique in this study used the observing and noting method. The listening method of this research was by reading the contents of the novel and then listening to Andrea Hirata's Ordinary People novel to find personification language styles. The note-taking technique in this study was used to record listening results, namely the personification style of language found in the novel Ordinary People in the form of personification language style. The results of the study show that there are 12 personification language style data in Andrea Hirata's Ordinary People novel.